Local Policy Strategies in Responding to Economic Inequality in Wasur Village, Merauke Regency, South Papua - Umiyati Haris; Eko Rachmat Saputro (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
This study examines the institutional dynamics influencing the economic conditions of Wasur Village, using Douglass North’s institutional economics perspective. It employs a descriptive qualitative approach, focusing on local strategy analysis through a case study of Wasur Village. Data were collected through in-depth interviews with purposively selected informants, including the Head of Wasur Village, the Head of BAMUSKAM, local community members, local entrepreneurs, and the Head of DPMK Merauke. The interviews were conducted to gather insights on the village’s economic policies, the strategies employed by the village government, and the challenges faced by the local community. The research data were analyzed thematically across five key themes: Economic Structure, Work Productivity and Consistency, Economic Inequality, Income Diversification, and the Strategies of the Wasur Village Government in Improving the Economy. The findings indicate that Wasur Village’s economic policies are centered on three programs, such as Sarang Semut, Minyak Kayu Putih, and Minyak Sereh Merah, which reflect the interests of the Wasur village government and the Wasur Village Hall, rather than the local community. The study reveals that economic challenges in Wasur are more influenced by weak institutional frameworks than by a scarcity of resources. These institutional shortcomings hinder productivity, exacerbate inequality, and limit income diversification, impeding the village's economic development. This study underscores the importance of strengthening local institutions to foster sustainable economic improvement in Wasur Village.Penelitian ini mengkaji dinamika kelembagaan yang mempengaruhi kondisi ekonomi di Kampung Wasur, dengan menggunakan perspektif ekonomi kelembagaan dari Douglass North. Pendekatan yang digunakan adalah deskriptif kualitatif, yang berfokus pada analisis strategi lokal melalui studi kasus di Kampung Wasur. Pengumpulan data dilakukan melalui wawancara mendalam dengan informan yang dipilih secara purposif, termasuk Kepala Desa Wasur, Kepala BAMUSKAM, anggota masyarakat lokal, pengusaha lokal, dan Kepala DPMK Merauke. Wawancara ini dilakukan untuk menggali wawasan mengenai kebijakan ekonomi desa, strategi yang diterapkan oleh pemerintah desa, serta tantangan yang dihadapi oleh masyarakat setempat. Data penelitian dianalisis secara tematik dengan lima tema utama: Struktur Ekonomi, Produktivitas Kerja dan Konsistensi, Ketimpangan Ekonomi, Diversifikasi Pendapatan, serta Strategi Pemerintah Desa Wasur dalam Meningkatkan Ekonomi. Hasil penelitian menunjukkan bahwa kebijakan ekonomi KampungWasur berfokus pada tiga program, yaitu Sarang Semut, Minyak Kayu Putih, dan Minyak Sereh Merah, yang lebih mencerminkan kepentingan pemerintah desa dan Balai Kampung Wasur, ketimbang kepentingan masyarakat setempat. Penelitian ini mengungkapkan bahwa tantangan ekonomi di Kampung Wasur lebih dipengaruhi oleh kelemahan institusi daripada kelangkaan sumber daya. Kelemahan kelembagaan ini menghambat produktivitas, memperburuk ketimpangan, dan membatasi diversifikasi pendapatan, sehingga menghalangi perkembangan ekonomi desa. Penelitian ini menekankan pentingnya penguatan institusi lokal untuk mendorong perbaikan ekonomi yang berkelanjutan di Kampung Wasur.